Change of soil chemical properties and the growth of Pogostemon cablin Benth on nickel-mined soil amended with rice husk charcoal - Suleman, Darwis; Resman, Resman; Syaf, Hasbullah; Namriah, Namriah; Suaib, Suaib; Alam, Syamsu; Yusuf, Dewi Nurhayati; Mbay, Wa Ode Nurmashita (Journal of Degraded and Mining Lands Management, 2024)
Nickel is an important main resource mineral in Southeast Sulawesi, which has deposited around 97.4 billion tons, and undoubtedly, nickel exports emerged in national and regional economic growth. Mining activities were carried out through topsoil and subsoil stripping, resulting in damage to the soil ecosystem and making it difficult for soil to recover. A study was performed to evaluate the changes in soil chemical properties and the growth of patchouli (Pogestemon cablin Benth) on nickel-mined soil treated with rice husk charcoal (RHC). A randomized block design was applied in this study, including six treatments of RHC with three replications. The treatments were without RHC (control), 1.5%, 3.0%, 4.5%, 6%, and 7.5% of soil weight. Data were analyzed descriptively for soil chemical properties; meanwhile, ANOVA was applied for plant growth. The results revealed that RHC increased soil pH, organic C, CEC, and available P, and conversely, the application of 4.5% of RHC decreased soil Ni and Fe content by 65.43% and 40.47%, respectively. The application of RHC up to 6% increased significantly the plant height and number of leaves as well as the dry weight of patchouli. The present study concluded that the use of carbon-rich soil conditioners such as rice husk charcoal is an imperative measure to restore the nickel-mined soil.